2003
DOI: 10.1161/01.hyp.0000058001.67791.0a
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Concentric Geometry as a Risk Factor in Gestational Hypertension

Abstract: Abstract-In the past, an adverse prognostic significance of an altered left ventricular geometry in essential hypertension has been demonstrated. There are no data on the prognostic significance of an altered cardiac structure during pregnancy. The present study was designed to evaluate the prognostic impact on the outcome of pregnancy of an altered geometry of the left ventricle in mild gestational hypertension. One hundred forty-eight consecutive, pregnant, mild gestational hypertensive women (systolic and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 30 publications
(29 reference statements)
5
56
0
2
Order By: Relevance
“…Moreover, the finding of an elevated postpartum TVR and BP values in all of the women with an abnormal outcome compared with the uneventful group might indicate a possible pregestational predisposition to pregnancy complications, as hypothesized previously. 22,23 This hypothesis is strengthened in this study by the fact that differences in left ventricular morphological parameters and TVR were still present 6 to 8 months postpartum. Our study shows that, before complications appear, the maternal vascular function and cardiac morphology of pregnant patients destined to have complications differ dramatically from those destined to have a normal outcome of pregnancy and that this cardiovascular dissimilarities might be used to reliably classify them, in particular through TVR.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Moreover, the finding of an elevated postpartum TVR and BP values in all of the women with an abnormal outcome compared with the uneventful group might indicate a possible pregestational predisposition to pregnancy complications, as hypothesized previously. 22,23 This hypothesis is strengthened in this study by the fact that differences in left ventricular morphological parameters and TVR were still present 6 to 8 months postpartum. Our study shows that, before complications appear, the maternal vascular function and cardiac morphology of pregnant patients destined to have complications differ dramatically from those destined to have a normal outcome of pregnancy and that this cardiovascular dissimilarities might be used to reliably classify them, in particular through TVR.…”
Section: Discussionsupporting
confidence: 54%
“…In recent years, maternal cardiac function was studied in normal and complicated pregnancy obtaining important information on systolic and diastolic function and on morphological parameters of the left ventricle. [13][14][15][16][17][18][19][20][21][22][23] In particular total vascular resistance (TVR) was found to be an important parameter in the early identification of hypertensive patients who subsequently developed complications. 22 In our previous pilot study, 24 we observed that normotensive high-risk patients with bilateral notch of the uterine arteries who subsequently showed abnormal outcome of pregnancy had higher TVR compared with the normal-outcome group.…”
mentioning
confidence: 99%
“…21,22 Although some echocardiographic studies showed that women developing hypertensive complications during pregnancy may have different LA dimensions than controls, [23][24][25][26] the potential link between LA abnormality detected early in pregnancy by echocardiography or ECG and development of hypertensive disorders remains elusive. However, some possible mechanisms are supported by epidemiological data and experimental models.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of fetal growth restriction, end-diastolic volume, stroke volume, cardiac output, left ventricular mass, and left atrial function were demonstrated to be reduced compared with normal patients, while IVRT was prolonged 13 . Some of these changes may even precede the onset of the full clinical syndrome: Novelli and colleagues found left ventricular concentric geometry to be significantly associated with adverse outcome in women with gestational hypertension 15 , and the same group showed that in women with fetal growth restriction compared to normal fetuses, indices of systolic and diastolic ventricular function are depressed 16 . It is now established that in women who develop preeclampsia, the subsequent lifetime risk of death from cardiovascular disease is eight-fold higher than in those with a normal pregnancy.…”
Section: Discussionmentioning
confidence: 99%